2018
DOI: 10.1007/s11249-018-1039-5
|View full text |Cite
|
Sign up to set email alerts
|

Shear Thinning and Hydrodynamic Friction of Viscosity Modifier-Containing Oils. Part I: Shear Thinning Behaviour

Abstract: Viscosity versus shear rate curves have been measured up to 10 7 s −1 for a range of VM solutions and fully formulated oils of known composition at several temperatures. This shows large differences in the shear thinning tendencies of different engine oil VMs. It has been found that viscosity versus shear rate data at different temperatures can be collapsed onto a single master curve using time-temperature superposition based on a shear rate shift factor. This enables shear thinning equations to be derived tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…In a companion paper, the temporary shear thinning behaviour of a series of VM-containing blends was investigated, including both simple solutions in base oil and full engine oil formulations [1]. It was found that, with one exception, time-temperature superposition could be used to derive a single equation to describe the viscosity of the VM blend at any shear rate and temperature for a given blend.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a companion paper, the temporary shear thinning behaviour of a series of VM-containing blends was investigated, including both simple solutions in base oil and full engine oil formulations [1]. It was found that, with one exception, time-temperature superposition could be used to derive a single equation to describe the viscosity of the VM blend at any shear rate and temperature for a given blend.…”
Section: Introductionmentioning
confidence: 99%
“…This enables the influence of the VM additive on both hydrodynamic film thickness and hydrodynamic friction to be predicted for the oils studied in [1], and the ways that VMs contribute to friction reduction to be determined.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations